KEY FACTORS FOR PROMOTING ENTREPRENEURSHIP AT THE LOCAL LEVEL - TERENIAK, Liliya; KHARCHENKO, Pavlo (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article examines the role of local governments in promoting entrepreneurship at the local level. An analysis of the situation in most local governments revealed that it is small private enterprises that provide them with significant revenues to the local budget, the share of which often exceeds revenues from state-owned enterprises and formerly privatized complexes.Among the problems that arise in the interaction of structural units of administrations with business entities are, first of all, the lack of a well-established dialogue, mutual understanding, which is caused by a lack of information, partly due to rapidly changing legislation, and the lack of institutionalized principles of this dialogue. Another problem is that entrepreneurs do not have permanent partners in administrations, people or departments to whom they can turn to on any issue at any time. Without this, it is out of the question to build trust in the administration on the part of entrepreneurs, to create an atmosphere of openness and clarity.The most important obstacles to the widespread introduction of the competitive public procurement mechanism are the untimely adoption of local budgets and the lack of civilized, transparent methods and rules for placing procurement. In addition, the development of competition through these procedures is significantly hampered by the strong and actively lobbied interests of not only certain agencies, but also individual officials, and sometimes by the merger of business entities with these agencies. This requires the creation of a system of control over the correctness of public procurement placement, as well as sanctions for violation of the principles and procedure of placement.In preparing for the future, it is necessary to respond to both traditional and new challenges associated with the war: destruction of infrastructure, reduced demand for goods and services, human resources problems, lack of working capital financing, and logistical problems.
Keywords: entrepreneurship; local self-government; economic development of territories; administrative-territorial unit; public procurement; partnership